2014
DOI: 10.1021/jp502826e
|View full text |Cite
|
Sign up to set email alerts
|

A Three-Step Kinetic Model for Electrochemical Charge Transfer in the Hopping Regime

Abstract: Single-step nonadiabatic electron tunneling models are widely used to analyze electrochemical rates through self-assembled monolayer films (SAMs). For some systems, such as nucleic acids, long-range charge transfer can occur in a "hopping" regime that involves multiple charge transfer events and intermediate states. This report describes a three-step kinetic scheme to model charge transfer in this regime. Some of the features of the three-step model are probed experimentally by changing the chemical compositio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 65 publications
(130 reference statements)
0
9
0
Order By: Relevance
“…Our understanding of the charge transfer mechanism is based on a three-step process. 47 The first step is the charge generation by the illuminated nanoparticles and the charge injection into the DNA chain after crossing an electron injection barrier; the second step is the actual charge transfer through DNA until it reaches the reaction point. The third step is charge usage by an acceptor group, in our case 8BrdA.…”
Section: Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our understanding of the charge transfer mechanism is based on a three-step process. 47 The first step is the charge generation by the illuminated nanoparticles and the charge injection into the DNA chain after crossing an electron injection barrier; the second step is the actual charge transfer through DNA until it reaches the reaction point. The third step is charge usage by an acceptor group, in our case 8BrdA.…”
Section: Results and Discussionmentioning
confidence: 99%
“…From the three charge transfer steps, usually the charge injection is considered the rate-limiting step for the charge transfer, with an energy barrier which can vary between 0.2 and 0.4 eV. 47 , 52 …”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 2 shows molecular structures for the two linker types. 34 In contrast, if the charge transport proceeds coherently, then the decomposition into resistances for each step is no longer possible; rather the transport should be viewed as a product of transmission probabilities for each step. In recent work on DNA conductance, Tao and coworkers showed that the use of an amino thymidine nucleoside linker significantly increased the conductance relative to a thiol linker.…”
mentioning
confidence: 99%